Penguatan E-Government Dalam Pelayanan Publik Di Kelurahan Oluhuta - Alhadar, Sofyan; M. Yunus, Abd. Rahmat; Laparaga, Jefri; Ibrahim, Hasan; Ryan, Ahmad (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to strengthen the implementation of E-Government in public services at Oluhuta Village, with a focus on two main topics: the Context of E-Government in Village Governance and the Context of Challenges and Opportunities in E-Government. The activity involved village officials and the community in presentation sessions and in-depth discussions about the benefits, challenges, and opportunities that can be gained through the implementation of E-Government. The method used in this service is a participatory approach, with direct delivery of materials through presentations and interactive discussions. The results of this service show that village officials have begun to understand E-Government as a solution to improve administrative efficiency and public services. Additionally, the community also realizes that the implementation of E-Government can facilitate easier access to public services online. Despite challenges such as limited infrastructure and low technological literacy, significant opportunities such as increased transparency, accountability, and public participation in governance have also been identified. Overall, this community service successfully enhanced the understanding of both parties and raised awareness about the importance of E-Government in improving the quality of public services.